Colouring Cape Breton “Celtic”: Topographies of Culture and Identity in Cape Breton Island - Ivakhiv, Adrian (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2005)
This article rethinks the relationship between cultural identity and landscape by way of a post-constructivist, “multicultural political ecological” examination of Cape Breton Island’s Celtic Colours International Festival. The author reads the festival as an intervention on several levels: as part of a set of contests and contrasts by which Cape Bretoners articulate their identities and heritages; as a medium by which Celticity is defined and shaped as a transnational cultural discourse; as one arm of a strategy by which island entrepreneurs are repositioning Cape Breton as central within global tourist flows; and as a means by which a relatively cold northern landscape is made attractive through a discursive linkage with the pleasing imagery of autumn foliage in scenic mountain and highland topography. In the process, what was once the most industrialized region of the Atlantic Provinces can now boast an expressive harmony between “nature” and “culture”.